Pemodelan Hidrologi-Hidrodinamika 2D untuk Karakterisasi Genangan dan Bahaya Banjir Perkotaan di DAS Ampal, Balikpapan - Noor Zaqiyah Muhding; Umboro Lasminto (AGREGAT, 2026)
Flooding is a dominant hydrometeorological hazard in urban areas of Indonesia, including Balikpapan City as a strategic buffer zone for the Nusantara Capital City (IKN). This study aims to evaluate the performance of an integrated 2D hydrological–hydrodynamic model in representing the flood event of March 7, 2025, and to simulate flood inundation distribution and hazard levels based on inundation depth in the Ampal Watershed. The methodology employed hydrological modeling using HEC-HMS and two-dimensional hydrodynamic modeling using HEC-RAS 2D with an unsteady flow scheme. Calibration results indicate good model performance, with a Root Mean Square Error (RMSE) of 0.082 m, indicating low model error, and a Nash–Sutcliffe Efficiency (NSE) of 0.865, indicating good model performance. The model showed good agreement in representing the analyzed flood event. Simulation results indicate that inundation was concentrated along the Klandasan Besar River, with the maximum inundation depth identified in the Beller residential area. Flood hazard classification based on inundation depth shows that the very high hazard class (>0.50 m) covered 48.81 ha, while safe areas (<0.10 m) covered 92.04 ha and were generally located at higher elevations. The inundation pattern indicates concentrated overflow in low-lying and sink areas along the Klandasan Besar River corridor due to limited channel capacity, channel constriction (bottleneck), dominance of impervious surfaces, and backwater effects in downstream areas. The results of this study can support flood hazard mapping and urban flood mitigation planning in Balikpapan City.